Robert L. Hathaway, Not necessarily Cervantes: Readings of the "Quijote". Juan de la Cuesta, Newark, 1995; 190 pp. - Anthony Close (Nueva Revista de Filología Hispánica, 1997)
Se reseñó el libro: Not necessarily Cervantes: Readings of the "Quijote".